(untitled) - Cipolla, Carlo M. (New York, 1979)
Phylum Chordata evolved in ancient seas over 510 million years ago, as evidenced by fossils discovered in the Burgess Shales. Examines the unifying characteristics and their amazing evolutionary story.
Keywords: Công nghệ,Technology; Lịch sử,History